# Let f and g be the functions given by f(x) = e^{x} and g(x) = lnx. Find the function f(g(x)).

We will use the concept of functions in order to find f(g(x)).

## Answer: f(g(x)) = x

Let us see how we will use the concept of functions in order to find f(g(x)).

**Explanation:**

Given that, f(x) = e^{x} and g(x) = lnx.

In order to find composite function f(g(x)), we have to substitute x by g(x) in the function f(x) = e^{x}.

On substituting, we get that f(g(x)) = e^{ln(x)}

Now using the logarithmic property that is a^{log x} = x, we get f(g(x)) = e^{ln(x) }= x